Crocodile farming: a fresh approach - Reader, Robert, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
South Africa Crocodile Farmers are generally in a favourable position regarding the farming of this protected natural resource. It has eliminated the risks of the potentials of extinction of this prehistoric animal and ensured sustainable farming practises through good farming practises. The situation is now that this animal can be traded in theory similar to any stock domestic animals. Traceability is however a future requirement and we are measured by end consumer. The demand for high quality skins is still there and farmers can obtain good margins on these skins. The other grades are where the demand is met with low prices but eventually all skins are consumed in the manufacturing environment but here we are price takers. Can we do better? The following are matters which require further discussion: · At what price is it still economically to produce second grade skins? · Rising energy cost has forced crocodile farmers to look for alternative ways of effectively heating and cooling facilities · Structure design- Indoor/intensive farming or external/semi extensive farming · Integrated systems versus specific concentration · Probiotic · Free food/chicken mortalities, dry mix or combination · Abattoir or not · Export of wet or tanned skins · Quality or quantity · DEAT or Agriculture · Own Breeder Stock or hatchling/yearling purchasing · Agent or own marketing · The role of cooperation · Lessons from the poultry Industry
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.